Effects of a Self‐Regulated Cooperative Programming Approach on Elementary Students' Programming Knowledge, Metacognitive Awareness, and Self‐Efficacy. - Liu, Chengye; Cui, Zhihao; Weng, Xiaojing (Journal of Computer Assisted Learning, 2026)
Background: Programming is a vital digital skill that can equip students with the necessary competencies for future employment opportunities. However, due to inadequate metacognitive awareness, self‐regulation abilities, and a lack of prior programming knowledge, elementary school students may struggle with completing complex programming tasks. Objectives: We aim to propose a self‐regulated cooperative programming (SR‐CoP) approach. While exploring the effectiveness of the approach in students' programming knowledge, metacognitive awareness, and self‐efficacy. Methods: Participants were 113 fourth graders (54 males, 59 females). Their ages ranged from 10 to 11 years. They were randomly assigned to three groups: the control group using individual programming (C‐IdP), experimental group 1 employing SR‐CoP, and experimental group 2 employing conventional cooperative programming (C‐CoP). Results: The SR‐CoP approach significantly enhanced students' metacognitive awareness and self‐efficacy compared to the other groups. Regarding programming knowledge, no statistically significant difference were found among the three groups, suggesting that SR‐CoP supports non‐cognitive outcomes without compromising domain knowledge acquisition. Conclusions: By employing self‐regulation strategies, students engage in planning, self‐monitoring, and self‐reflection during project completion and cooperative programming activities. This practice is advantageous for enhancing elementary students' metacognitive awareness and self‐efficacy. Lay Summary: What is currently known about this topic?: The importance of programming education in developing 21st‐century skills is increasing, yet many learners still find it challenging.Cooperative learning has the potential to improve students' programming performance.The effectiveness of cooperative programming is closely related to students' self‐regulation, which are particularly important for younger learners. What does this paper add?: Designed and assessed the SR‐CoP approach for programming education.This study used quasi‐experiments to understand how self‐regulated learning could support cooperative programming among elementary school students. Implications for Practice/or Policy: The SR‐CoP approach provides programming educators with a practical pedagogy.This study offers empirical evidence for cooperative programming learning and extends the research scope of self‐regulated learning.